Coronavirus-2019-related multisystem inflammatory syndrome in adults: A descriptive cross-sectional study - K. C. Mridula Varma; Jijith Krishnan; C. V. Sonia George; B. A. Haseena (Journal of Clinical and Scientific Research)
Background: The multisystem inflammatory syndrome in adults (MIS-A) may develop several weeks after severe acute coronavirus-2 (SARS-CoV-2) disease (COVID-19). The objective of the study was to evaluate the clinical and biochemical findings of COVID-19-related MIS-A patients. Methods: This descriptive cross-sectional study was conducted among patients with confirmed COVID-19-related multisystem inflammatory syndrome. Data related to demographics and duration for symptoms, laboratory investigations, duration of intensive care unit stay, ventilator support, COVID-19 treatment medications, vaccination status and clinical outcomes were collected. Results: A total of 19 patients with confirmed COVID-19-related MIS-A were included in the study. Of these, majority of the patients were men (12/19). The most common presenting symptoms were fatigue (n = 19), fever (n = 17), dyspnoea (n = 13), myalgia (n = 12), icterus (n = 12), vomiting (n = 12) and oedema (n = 12). The onset of symptoms occurred 3–6 weeks after exposure to COVID-19 (8/19). Anaemia (haemoglobin < 10 g/dL) was observed in 11 patients. Approximately one-third of patients (15/19) showed marked thrombocytopenia. An increasing trend in levels of D-dimer and albumin was observed in the majority of patients (13/19 and 15/19, respectively). Elevated aspartate aminotransferase (AST) and alanine aminotransferase (ALT) (>500 U/L) levels were observed in 3 and 2 patients, respectively. The average length of hospital stay was 9.7 days. Seventeen patients had improved; 2 patients died. Conclusions: Occurrence of elevated leucocytes, D-dimer, AST and ALT and reduced haemoglobin, platelet count and albumin were observed in COVID-19-related MIS-A patients. Therefore, these parameters have potential for being used for early diagnosis of MIS-A.